An outbreak of methicillin resistant Staphylococcus epidermidis among neonates in a hospital in Saudi Arabia - Abd El Hafez, Maha; Khalaf, Noha G.; El Ahmady, Mohamed; Abd El Aziz, Ahmed; Hashim, Abd El Gawad (The Journal of Infection in Developing Countries, 2011)
Introduction: Staphylococcus epidermidis is a pathogen associated with nosocomial infection in neonatal intensive care units (NICU). This study investigates an outbreak of methicillin resistant S. epidermidis in an NICU in a hospital in Saudi Arabia. Methodology: A total of 41 isolates identified as Gram-positive cocci were obtained from blood culture, umbilical wound swabs and endotracheal aspirate specimens of neonates, of which 29 were identified as S. epidermidis. Bacterial identification at the species level and determination of antibiotic resistance were performed by MicroScan (Dade Behring, USA). Genotyping was completed using randomly amplified polymorphic DNA (RAPD) and the mecA gene was detected by PCR. Results: All 29 S. epidermidis isolates were found to be resistant to oxacillin and were positive for the mecA gene. The isolates showed several multidrug-resistance patterns; the resistance rates to gentamicin, erythromycin, clindamycin, and trimethoprim/sulfamethoxazole were 89.7%, 86.2%, 75.9% and 72.4%, respectively. All isolates were susceptible to vancomycin, teicoplanin, rifampin, synercid, and ciprofloxacin. Several genotypic and phenotypic patterns were detected among the S. epidermidis isolates: antibiogram typing showed seven different patterns, one of which was shared by 65% of the isolates, whereas the most prevalent RAPD genotype was shared by only five S. epidermidis isolates, and did not correlate with antibiotic resistance phenotype. Conclusion: The diverse clonal origin of tested isolates indicates the presence of multiple S. epidermidis strains among neonates in the NICU setting